1996
DOI: 10.1007/bf01709527
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intra-arterial blood gas monitoring

Abstract: Over the past 10 years a number of continuous intra-arterial blood gas monitoring systems have been developed. The performance characteristics of these systems are comparable. Their levels of accuracy as measured in bench tonometry are not consistently achieved in clinical trials. The potential usefulness of these monitors in various clinical situations has been described in case studies. Controlled studies demonstrating an improvement in outcome with the use of these monitors have not been published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The flush solution, at room temperature, contains dissolved oxygen and carbon dioxide at partial pressures similar to that of the atmosphere thus it may alter the local gas tension. As a consequence, the system may measure the blood gas variables in the flush solution, resulting in errors known as the "flush effect" [1,42]. The CDI™ 500 was highly reliable even when the flow decreased significantly during vasoconstriction in contrast with IABG systems which are susceptible to blood flow and when it is low or stops measurements become unreliable [1].…”
Section: Discussionmentioning
confidence: 99%
“…The flush solution, at room temperature, contains dissolved oxygen and carbon dioxide at partial pressures similar to that of the atmosphere thus it may alter the local gas tension. As a consequence, the system may measure the blood gas variables in the flush solution, resulting in errors known as the "flush effect" [1,42]. The CDI™ 500 was highly reliable even when the flow decreased significantly during vasoconstriction in contrast with IABG systems which are susceptible to blood flow and when it is low or stops measurements become unreliable [1].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available tonometers have equilibration periods ranging between 10 and 90 min [16,17,18,19] and are therefore not efficient for rapid detection of changes in tissue perfusion on a continuous basis. Fiberoptic sensors that are used in clinical medicine for automatic and continuous measurements of blood gases [43,44] have a rapid response time [45]. Experimental evaluation of a fiberoptic P CO 2 sensor, similar to that used in the present study, has shown a high degree of precision in detecting short-term changes in intramucosal P CO 2 [35].…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence quenching on exposure to oxygen provides an attractive approach to the development of an oxygen sensor. In the past two decades, two continuous intravascular blood gas monitoring (CIBM) systems, Paratrend 7+ (Diametrics Medical Inc., High Wycombe, UK) and Neotrend (Diametrics Medical Inc. High Wycombe, UK), have been developed based on a fluorescence quenching mechanism 5,10–12 . The Paratrend 7+ is a hybrid probe incorporating three different sensors: an optical fluorescent sensor to measure the partial pressure of oxygen (PO 2 ), optodes to measure the partial pressure of carbon dioxide (PCO 2 ) and pH.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, two continuous intravascular blood gas monitoring (CIBM) systems, Paratrend 7+ (Diametrics Medical Inc., High Wycombe, UK) and Neotrend (Diametrics Medical Inc. High Wycombe, UK), have been developed based on a fluorescence quenching mechanism. 5,[10][11][12] The Paratrend 7+ is a hybrid probe incorporating three different sensors: an optical fluorescent sensor to measure the partial pressure of oxygen (PO2), optodes to measure the partial pressure of carbon dioxide (PCO2) and pH. Neotrend, a modification of the Paratrend 7+, was designed for CIBM in the umbilical artery of newborn infants using the same sensors as in the Paratrend 7+.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation